Fibrinolytic status in acute coronary syndromes: Evidence of differences in relation to clinical features and pathophysiological pathways - Shantsila, Eduard; Montoro-Garcia, Silvia; Tapp, Luke D.; Apostolakis, Stavros; Wrigley, Benjamin J.; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2012)
Limited data are available on the role of innate fibrinolysis in acute coronary syndromes (ACS). In the present study we evaluated the dynamic alterations of fibrinolytic markers in patients presenting with ACS. Tissue-type-(tPA) and urokinase type-(uPA) plasminogen activators, plasminogen activator inhibitor (PAI-1) antigen and activity and thrombin activatable fibrinolysis inhibitor (TAFI) were analysed in 50 patients with ST elevation myocardial infarction (STEMI), 47 non-STEMI patients (NSTEMI), 40 patients with stable coronary artery disease (CAD) and 39 controls. The parameters were measured on day 1 and days 3, 7 and 30. Counts of monocyte subsets, monocyte-platelet aggregates and plasma inflammatory cytokines were assessed on admission. On day 1, TAFI was higher in NSTEMI vs. STEMI (p<0.001) while PAI-1 activity was higher in STEMI (p<0.001). In STEMI, uPA activity levels was low on day 1 but significantly increased on day 30 (p<0.001). TAFI levels were increased in NSTEMI on day 1 and gradually reduced by day 30 (p<0.05). In STEMI, TAFI levels peaked at day 7 (p<0.05) and dropped significantly by day 30 (p<0.05). CD14++CD16+ monocytes were independently associated with PAI-1 activity in ACS (p=0.03). Monocyte-platelet aggregates rather than platelet-free monocytes were an independent determinant of tPA, PAI-1 antigen and TAFI on a multivariate analysis (p<0.05). There are significant differences in fibrinolytic activity between patients with STEMI and NSTEMI. These changes could reflect the role of these factors in post-MI myocardial healing. Monocyteplatelet interactions are independently associated with the regulation of the fibrinolytic status in ACS.Note: The editorial process for this article was fully handled by Prof. Christian Weber, Editor-in-Chief.
Keywords: Acute coronary syndromes; fibrinolysis; monocyte-platelet aggregates; monocyte subsets; non-ST-elevation myocardial infarction; ST-elevation myocardial infarction